Ancestry, Place[s], and Identity in Spiritual Direction Narratives - Ruffing, Janet Kathryn (Narrative Works, 2018)
In this 2017 John McKendy Memorial Lecture, Dr. Janet Ruffing, RSM, discussed spiritual direction as a narrative process, recognized or not, in which the directee tells his or her sacred tale in the interaction with a spiritual director who significantly affects the unfolding of this serial narrative of lived faith. At a time, when directees have unprecedented access to genealogical information and also live in or make retreats in a variety of places, how do these new experiences affect their identity spiritually and socially? Do they become integrated into the ongoing narrative of identity or not?